An experimental and numerical study of micro-grinding force and performance of sapphire using novel structured micro abrasive tool. (1st September 2020) - Sun, Y.; Su, Z.P.; Gong, Y.D.; Jin, L.Y.; Wen, Q.; Qi, Y.
Highlights: A novel structured micro abrasive tool with chip removal micro helical slots and the diameter less than 700μm is firstly designed and prepared by hybrid process aimed at reducing tool wear and increasing the service life of micro abrasive tool. The micro-grinding force model of structured micro abrasive tool considering the structural parameters, size effect and material removal mechanism is firstly established. Comparing with conventional micro abrasive tools, the micro-grinding force of sapphire specimens machined by new micro abrasive tool is significantly reduced and the surface quality is greatly improved. Abstract: Micro-grinding technology has more competitive advantages than other micro machining technologies in fabricating complex three-dimensional micro parts and micro structures on hard and brittle materials, but the service life of existing micro abrasive tool has become one of the key factors restricting the popularization and application of micro-grinding technology. In this study, a novel structured micro abrasive tool with chip removal micro helical slots and the diameter less than 700μm is designed and prepared by hybrid process aimed at reducing wear and tear and increasing the service life of micro abrasive tool. The micro-grinding force model considering the structural parameters, size effect and material removal mechanism is established, which can reflect the micro-grinding performance and wear resistance of the novel micro abrasive tool. The verified experimental results indicated that the micro-grinding force model can effectively predict time-domain variation of the novel structured micro abrasive tool, and the simulated grinding force signal within 150ms fluctuation range error can be confined to be 7%. Moreover, comparing with the conventional micro abrasive tool, the micro-grinding force of sapphire specimens machined by novel micro abrasive tool is significantly reduced. Besides, the novel micro abrasive tool shows better wear resistance with the increase of grinding times, the novel micro abrasive tool surface roughness increment ∆Ra1 and ∆Rz1 is decreased by 0.2μm and 10μm respectively, and the stability of micro grinding is markedly improved. This work might play an important role in promoting the parameterization and non-standardization design of micro abrasives tools. Graphical abstract: The preparation process, fabricated results and micro grinding force for novel abrasive tool. Image, graphical abstract